2021
DOI: 10.3390/ijms22126260
|View full text |Cite
|
Sign up to set email alerts
|

miR-373-3p Regulates Invasion and Migration Abilities of Trophoblast Cells via Targeted CD44 and Radixin

Abstract: Preterm labor (PTL) is one of the obstetric complications, and is known to be associated with abnormal maternal inflammatory response and intrauterine inflammation and/or infection. However, the expression of specific miRNAs associated with PTL is not clear. In this study, we performed combination analysis of miRNA array and gene array, and then selected one miRNA (miR-373-3p) and its putative target genes (CD44 and RDX) that exhibited large expression differences in term and PTL placentas with or without infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
(29 reference statements)
3
10
0
Order By: Relevance
“…Besides evidence of increased miR-373-3p levels in multiple cancers [34][35][36][37], research has demonstrated its upregulation in preterm labor placentas relative to normal placentas [13], a finding partially consistent with our observation in the placental tissues of smaller sIUGR fetuses. It is well-known that placentation relies heavily on the proliferative and migratory abilities of trophoblast cells [19]; therefore, any factors that alter these properties affect placental development.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Besides evidence of increased miR-373-3p levels in multiple cancers [34][35][36][37], research has demonstrated its upregulation in preterm labor placentas relative to normal placentas [13], a finding partially consistent with our observation in the placental tissues of smaller sIUGR fetuses. It is well-known that placentation relies heavily on the proliferative and migratory abilities of trophoblast cells [19]; therefore, any factors that alter these properties affect placental development.…”
Section: Discussionsupporting
confidence: 91%
“…It is well-known that placentation relies heavily on the proliferative and migratory abilities of trophoblast cells [19]; therefore, any factors that alter these properties affect placental development. The observations by Lee and colleagues, together with our findings of increased expression in placental tissues and a regulatory action on trophoblast cells, robustly support the key role of miR-373-3p in placental development [13]. This further highlights the significance of deregulated miRNAs, such as miR-210, miR-376c, and miR-455 [38][39][40], as well as miR-373-3p validated in this study, in the development of placenta-related disorders.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Consistent with the results, early studies have shown the crucial roles of miRNAs in the biological function of trophoblasts. For instance, miR-373-3p has been proved to suppress migration and invasion of trophoblasts by targeting CD44 and Radixin, 31 and Hayder et al. 21 highlighted that miR-210-3p upregulation could damage USAR-related biological functions of extravillous trophoblasts.…”
Section: Discussionmentioning
confidence: 99%